People and Computers XV—Interaction Without Frontiers 2001
DOI: 10.1007/978-1-4471-0353-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Interface: Co-evolution Inside Interactive Systems — A Proposal Founded on Activity Theory

Abstract: Task oriented and object oriented traditional interactive system design methods show more and more shortcomings in the light of recent evolutions. These evolutions are both external (organizational) and internal (technological) to the developed systems. The two main problems of traditional methods are their linearity and rigidity. Once a system has been introduced, it can only evolve through maintenance. These methods follow several steps segmenting time, actors, and work to be realised. Taking results from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
14

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 14 publications
1
28
0
14
Order By: Relevance
“…This approach would also support the user-system coevolution phenomenon [36,37]. In fact, it is often observed in HCI studies that ''using the system changes the users, and as they change they will use the system in new ways'' ( [38], p. 78).…”
Section: Enhancing Cmss With Eud Featuresmentioning
confidence: 88%
See 1 more Smart Citation
“…This approach would also support the user-system coevolution phenomenon [36,37]. In fact, it is often observed in HCI studies that ''using the system changes the users, and as they change they will use the system in new ways'' ( [38], p. 78).…”
Section: Enhancing Cmss With Eud Featuresmentioning
confidence: 88%
“…3.2, in HCI it has been observed that, once people gain proficiency in system usage, they would like to use the system in different ways and need evolved functionalities with respect to those they required when they were novice users. These new uses of the system make the working environment and organization evolve, and force the designers to adapt the system to meet the needs of the evolved end-user organization and environment [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these dimensions in SDEs is important and remains a non-trivial work. Moreover, we have been working for years in the CSCW research domain by using the AT [6] [7]. We have identified some other properties that have not really been taken into account in developing such systems.…”
Section: Previous Studies Using Atmentioning
confidence: 99%
“…This is not so surprising because learning and software development are both human activities. The approach we have developed has been synthesized under the co-evolution principle that we have defined in [7]. Co-evolution emphasizes the fact that human activity is reflective in the sense that any (cooperative) activity is closely linked to a (cooperative) meta-activity where the subjects co-construct their environment in response to contradictions emerging during the core activity.…”
Section: Adding Our Experiencementioning
confidence: 99%
“…Nos travaux s'inspirent de résultats provenant des Sciences Humaines et Sociales (SHS), en particulier la Théorie de l'Activité (TA), et s'attachent à proposer des modèles et systèmes offrant une malléabili-té en accord avec les propriétés expansives de toute activité humaine. Ces réflexions nous ont amené à définir le principe de Coévolution [ 6] qui est mis en avant dans la plate-forme naissante CooLDA [ 4].…”
Section: Introductionunclassified